Premises Of Creation In The Light Of The Psschal Eevent - Ciećko, Szymon Krzysztof (Studia Theologica Varsaviensia, 2019)
Author gives an answer to the question of how to understand creation in the light of Passover by referring primarily to the reflections by a contemporary Italian philosopher and theologian Giuseppe Maria Zanghí. The substance of the article consists of three points: the Easter trinitology, the ontological implications of the Paschal event and the premise of creation in the perspective of the Paschal event.